2011
DOI: 10.1177/1352458511422301
|View full text |Cite
|
Sign up to set email alerts
|

Posters II

Abstract: Objective: This study describes the frequency of lumbar punction in patients with newly diagnosed MS in clinical practice in 4 hospitals in the Netherlands from 2000 til 2010. Methods: NEDbase is a part of MSBase. NEDBase is a multiinstitutional database from the Netherlands, currently receiving data of 5 contributing centers using the iMed MS documentation software. Patients with onset of MS between 2000 and 2010 were identified retrospectively from NEDBase.Percentage of lumbar punction performed after the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…As mentioned, through its inhibition of DHO-DH, teriflunomide exerts a cytostatic effect on stimulated lymphocytes (7). In a study of human PBMCs stimulated in vitro , Li et al showed that teriflunomide principally affected proliferation of lymphocytes, with little effect on function (41), and teriflunomide-treated patients have been shown to mount effective responses to seasonal influenza vaccination (42). In an adoptive transfer model of EAE, in vitro teriflunomide treatment of MBP-specific T cells prior to transfer reduced maximal disease scores in recipient naïve animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned, through its inhibition of DHO-DH, teriflunomide exerts a cytostatic effect on stimulated lymphocytes (7). In a study of human PBMCs stimulated in vitro , Li et al showed that teriflunomide principally affected proliferation of lymphocytes, with little effect on function (41), and teriflunomide-treated patients have been shown to mount effective responses to seasonal influenza vaccination (42). In an adoptive transfer model of EAE, in vitro teriflunomide treatment of MBP-specific T cells prior to transfer reduced maximal disease scores in recipient naïve animals.…”
Section: Discussionmentioning
confidence: 99%
“…Teriflunomide’s effects on the proliferation of activated lymphocytes are expected to lead to decreased CNS inflammation (50). T-cell expansion within the CNS has been documented in the EAE model (51), so it will be important for future studies to establish whether teriflunomide affects the proliferation of T cells within the CNS in addition to its effects on T-cell proliferation in the periphery (41). Other immunomodulatory effects independent of pyrimidine synthesis that have been described for teriflunomide may also account for the reduction in DA rat spinal cord immunocytes observed in this study, including reduced T-cell chemotaxis (43), inhibition of protein aggregation (52), and weakening of T-cell interactions with antigen-presenting cells (53).…”
Section: Discussionmentioning
confidence: 99%